Constructing Structural Profiles for Protein Torsion Angle Prediction - Aydin, Zafer; Baker, David A.; Noble, William Stafford (SciTePress, 2015)
Structural frequency profiles provide important constraints on structural aspects of a protein and is receiving a growing interest in the structure prediction community. In this paper, we introduce new techniques for scoring templates that are later combined to form structural profiles of 7-state torsion angles. By employing various parameters of target-template alignments we improve the quality and accuracy of structural profiles considerably. The most effective technique is the scaling of templates by integer powers of sequence identity score in which the power parameter is adjusted with respect to the similarity interval of the target. Incorporating other alignment scores as multiplicative factors further improves the accuracy of profiles. After analyzing the individual strengths of various structural profile methods, we combine them with ab-initio predictions of 7-state torsion angles by a linear committee approach. We show that incorporating template information improves the accuracy of ab-initio predictions significantly at all levels of target-template similarity even when templates are distant from the target. Template scaling methods developed in this work can be applied in many other prediction tasks and in more advanced methods designed for computing structural profiles. © 2020 Elsevier B.V., All rights reserved.
Institute for Systems and Technologies of Information, Control and Communication (INSTICC)
Keywords: Profile-Profile Alignment; Protein Torsion Angle Prediction; Structural Frequency Profiles; Template Scoring; Alignment; Biomedical Engineering; Forecasting; Proteins; Torsional Stress; Ab Initio Prediction; Individual Strength; Multiplicative Factors; Profile Alignment; Structural Frequencies; Structure Prediction; Template Scoring; Torsion Angle; Bioinformatics